STUDI LITERATUR : SCOPING REVIEW GAMBARAN FAKTOR DALAM PREHOSPITAL DELAY PADA PASIEN STROKE - Hakiki, Siti Nur; Cecep Eli Kosasih; Anita Setyawati (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah., 2021)
ABSTRACTPrehospital delay in stroke patients occurs after 3-4.5 hours after onset, which can lead to worsening patient's condition if not treated quickly. Prehospital delay influenced by various factors, the aim of this study was to determine the factors of prehospital delay in stroke patients.This study was done with scoping review method by using Google Scholar, Pubmed, Sciencedirect, Ebsco and Researchgate database. The steps of this study consisted of: 1) Questions Identification, 2) Articles Identification, 3) Articles Screening, 4) Data Mapping, 5) Results Compilation, and 6) consultation. 1599 articles were selected based on titles, abstracts, contents, and results according to the inclusion criteria and objectives of this literature study. The screening results were translated into a literature review chart so that 13 articles were obtained and were further analyzed using JBI Critical Appraisal. Inclusion criteria defined were: full text articles, focus of discussion on factors of prehospital delay in stroke patients, as well as population and samples of stroke patients that were over 18 years and/or their family. This scoping review showed factors that affected prehospital delay in stroke patients were respondent characteristics, distance traveled, stroke symptoms, transportation system, treatment facility, and stroke awareness. An effective transportation system, proper recognition of stroke symptoms, good stroke awareness supported by education and income levels can prevent prehospital delay in stroke patients. However, further research is needed to thoroughly examine the effect these factors on the prehospital delay in stroke patients. Keyword: Adult Stroke, Prehospital Delay, Stroke PatientsBibliography : 77, 1978-2020